The role of credit market friction in trade-dependent small open economy : examination of South Korea business fluctuations with DSGE approach - Chen, Shuai (2017)
Recent literature suggests that credit market friction has a significant impact on the sources of the United States and Canadian business cycle. Our paper incorporates credit market friction and revised capital price in a small open economy DSGE model, and introduces a new entrepreneur’s equity shock. We examine the impact of credit market friction on macroeconomic environment in South Korea through decomposition of shocks and impulse responses analysis. We demonstrate improved robustness and identify foreign interest rate shock and import-cost push shock with more severe effect on macroeconomic fluctuations. Our findings suggest that a small open economy is more vulnerable to external shocks when credit market friction is considered.